EATING OUTSIDE HOME DURING PANDEMIC: PERSPECTIVE BASED ON HEALTH BELIEF MODEL AND FUTURE IMPLICATIONS - Rachmah, Qonita; Atmaka, Dominikus Raditya; Nindya, Triska Susila; Megatsari, Hario; Nor, Norfezah Md (Universitas Airlangga, 2025)
The COVID-19 pandemic has led to a significant decline in eating outside the home (EOH). This study aimed to compare eating habits before and after the pandemic using the Health Belief Model (HBM) to explore the implications of EOH and its potential long-term effects. A quantitative cross-sectional design was employed, involving 401 young adults aged 18–25 years living in Indonesia, selected through accidental sampling. Data on the participants’ general characteristics, EOH frequency, and health beliefs were collected online using SurveyMonkey. Descriptive statistics were used to summarize each variable, and binary logistic regression was conducted to identify the predictors of EOH behavior and frequency. The majority of the respondents were female, unmarried, and held a diploma or undergraduate degree. Nearly 40% reported weight gain during the pandemic, although the frequency of EOH significantly declined (p < 0.000). The frequency of EOH was significantly associated with self-efficacy in eating at home, perceived severity, perceived benefits, and perceived barriers (p < 0.05). In conclusion, understanding the underlying factors contributing to reduced EOH is crucial. Enhancing self-efficacy, emphasizing the benefits of home eating, and addressing perceived risks and barriers may help promote healthier eating behaviors among young adults.